2020
DOI: 10.1371/journal.pone.0238321
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the WHO group interpersonal therapy for people living with HIV/AIDS in Northwest Ethiopia: A qualitative study

Abstract: Background Psychological treatments improve depressive symptoms in people living with HIV/AIDS (PLWHA). Adaptation of treatments should be based on explanatory models of depression and other elements within the given context. Aim This study aimed to examine explanatory models of depression and acceptable approaches for implementation of group IPT in Northwest Ethiopia. Methods Qualitative data were collected from April to May 2019 from case managers, adherence supporters and service users using focus group dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…After further discussions with the trainers and supervisors, we decided that the most suitable people to do the counselling were the adherence supporters and case managers. Case managers and adherence supporters were most suitable to provide the intervention because of their shared lived experiences with difficult life circumstances, views about cause and treatment of depression, and to minimize stigma and maintain confidentiality [21]. In our prior study results, we found that case managers and adherence supporters viewed psychosocial problems as the main cause of depression.…”
Section: Selection Of Trainers Supervisors and Potential Counsellorsmentioning
confidence: 93%
See 3 more Smart Citations
“…After further discussions with the trainers and supervisors, we decided that the most suitable people to do the counselling were the adherence supporters and case managers. Case managers and adherence supporters were most suitable to provide the intervention because of their shared lived experiences with difficult life circumstances, views about cause and treatment of depression, and to minimize stigma and maintain confidentiality [21]. In our prior study results, we found that case managers and adherence supporters viewed psychosocial problems as the main cause of depression.…”
Section: Selection Of Trainers Supervisors and Potential Counsellorsmentioning
confidence: 93%
“…We used peer-administered group IPT intervention with eight weekly sessions for treatment of depressive symptoms and examined the acceptability and feasibility of the group IPT for PLWHA in Ethiopia. A detailed description of the setting is available elsewhere [21]. This paper reports on a feasibility and acceptability pilot study.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…IPT has been adapted for treatment of disorders such as bipolar disorder, bulimia nervosa and posttraumatic stress disorder, and for use among adolescents, the elderly and people with HIV ( Lipsitz, 2013 ). It has been implemented in diverse cultural contexts such as China ( Gao et al, 2010 ), Uganda ( Bolton et al, 2003 , 2007 ; Mutamba et al, 2018 ), Ethiopia ( Asrat et al, 2020 ) and Hispanic populations in the US ( Markowitz et al, 2009 ). The recent popularity of IPT coincided with its inclusion in the World Health Organisation (WHO) mental health Gap Action Programme (mhGAP) guide for the management of depression, and with the publication of the WHO group IPT intervention manual for low-resource, community settings ( World Health Organization, 2016 ; World Health Organization and Columbia University, 2016 ).…”
Section: Introductionmentioning
confidence: 99%